Model Pengukuran Kualitas Audit Internal (Studi Pada Auditor Internal Pada Perusahaan Swasta, BUMD dan BUMN di Kota Medan) - Novien Rialdy; Maya Sari; Edisah Putra Nainggolan (Universitas Samudra, 2020)
The purpose of this study is to analyze the internal audit quality measurement model, with a study of internal auditors in private companies, BUMD and BUMN in Medan City. Determination of sample size is obtained by multiplying the number of construct variables with the total number of indicators, so as to obtain 170 people. Primary data were collected through questionnaire distribution techniques, and analyzed using Structural Equation Modeling method. The results of this study prove that there is a significant direct effect on independence, competence and motivation on due professional care; and there is a significant influence of independence, competence, motivation and due professional care on audit quality. Moreover, the results of this study found that indirectly, independence, competence and motivation proved to significantly influence audit quality through due professional care.